Water in nanoporous hexagonal boron nitride nanosheets: a first-principles study - Gonçalves, Juliana A.; Batista, Ronaldo J. C.; Barbosa, Marcia C. (Beilstein Journal of Nanotechnology, 2025)
Nanoporous membranes are being explored as efficient materials for water filtration and desalination applications. In this study, we analyzed the behavior of pores within a freestanding hexagonal boron nitride (h-BN) monolayer in contact with water molecules. Our investigation revealed that triangular and rhombic pores induce wrinkles in non-deposited h-BN monolayers because of the repulsion between hydrogen orbitals at their 60° vertices. We found that the addition of N–H or B–H pairs at 60° vertices mitigates these out-of-plane deformations. Surprisingly, the stability of triangular pores with N–H termination is significantly increased by the addition of B–H pairs, whereas the stability of triangular pores with B–H termination is decreased by the addition of N–H pairs, indicating a distinct evolution of the pore shape based on the initial edge termination. Furthermore, we observed that the combination of H and OH is more effective in stabilizing the edges of rhombic pores compared to using only H atoms, whereas the opposite is true for small triangular pores that cannot accommodate the ·OH radical. Our findings also demonstrate that rhombic pores have a high affinity for water absorption, much higher than that of triangular pores. This suggests that the type of pore can significantly alter the hydrophobicity of h-BN and influence water flow through the membrane. Additionally, we observed that water molecules tend to form hydrogen bonds with the N–H-terminated surface in rhombic pores, but not with the B–N-terminated surface, potentially leading to asymmetries in water flow through the pore area. Overall, our study provides valuable insights into the interaction between nanoporous h-BN membranes and water.
Keywords: boron nitride; DFT; nanoporous materials; water